2015
DOI: 10.1242/jeb.117333
|View full text |Cite
|
Sign up to set email alerts
|

Learning context modulates aversive taste strength in honey bees

Abstract: The capacity of honey bees (Apis mellifera) to detect bitter substances is controversial because they ingest without reluctance different kinds of bitter solutions in the laboratory, whereas free-flying bees avoid them in visual discrimination tasks. Here, we asked whether the gustatory perception of bees changes with the behavioral context so that tastes that are less effective as negative reinforcements in a given context become more effective in a different context. We trained bees to discriminate an odoran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 55 publications
1
41
0
3
Order By: Relevance
“…The object detection threshold of different psyllid species was tested in a V-shaped maze, which was adapted from a conventional Y-shaped maze previously used to test free-flying insects (Giurfa et al, 1996(Giurfa et al, , 1997Reisenman and Giurfa, 2008) and, more recently, walking insects (Yilmaz et al, 2014;de Brito Sanchez et al, 2015). Experiments were conducted in a controlled laboratory chamber surrounded by white fabric curtains and illuminated from the top by four Philips Master TLSHE slimline 28W/865UV+ daylight fluorescent tubes (Philips, The Netherlands) with specially fitted highfrequency (1200 Hz) ATEC Jupiter EGF PMD2614-35 electronic dimmable ballasts.…”
Section: Y-maze Bioassaymentioning
confidence: 99%
“…The object detection threshold of different psyllid species was tested in a V-shaped maze, which was adapted from a conventional Y-shaped maze previously used to test free-flying insects (Giurfa et al, 1996(Giurfa et al, , 1997Reisenman and Giurfa, 2008) and, more recently, walking insects (Yilmaz et al, 2014;de Brito Sanchez et al, 2015). Experiments were conducted in a controlled laboratory chamber surrounded by white fabric curtains and illuminated from the top by four Philips Master TLSHE slimline 28W/865UV+ daylight fluorescent tubes (Philips, The Netherlands) with specially fitted highfrequency (1200 Hz) ATEC Jupiter EGF PMD2614-35 electronic dimmable ballasts.…”
Section: Y-maze Bioassaymentioning
confidence: 99%
“…Studies in bees have shown that the shape of the generalization gradient obtained after differential conditioning (and in these cases, the magnitude of the peak shift) could vary according to some stimulus characteristics, such as the relative difference between the positive and the negative reinforcements or the relative frequency of CS+ and CS− trials [55,60]. This indicates that the width of excitatory and inhibitory gradients depends on these and probably other parameters [61]. For instance, in our case, a reinforcement more aversive than quinine or an increase of the number of CS− trials could have enlarged the width of the inhibitory generalization gradients, making them probably larger than the excitatory generalization gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Essas duas formas de condicionamento podem ser atingidas em dois tipos de abordagens: o condicionamento absoluto, no qual o animal é treinado com apenas um estímulo condicionado (EC+) seguido de recompensa (ENC); e o condicionamento diferencial, no qual o animal é apresentado a dois estímulos, um associado a uma recompensa (EC+) e um sem a recompensa ou com uma punição, como solução de quinina ou sal que são substâncias de sabor aversivo para as abelhas (EC-). A apresentação de punição ao animal pode melhorar o processo de discriminação entre estímulos, pois os custos de uma resposta errada são maiores (Sanchez et al 2015). Assim, no condicionamento diferencial, o animal deve associar um sinal à recompensa enquanto o outro sinal está associado a ausência de recompensa ou punição.…”
Section: O Papel Do Aprendizado E As Bases Do Condicionamentounclassified
“…O EC-pode ser a ausência de solução de sacarose, ou ainda, substâncias aversivas para as abelhas. Recomenda-se solução concentrada de cloreto de sódio (NaCl) nesses casos (Sanchez et al 2015). A apresentação de EC às abelhas, no caso do condicionamento olfativo, pode ser feita de forma precisa, com aparelhos controlados por microcomputadores (Szyszka et al 2014), o que permite um melhor controle experimental.…”
Section: Resposta Da Extensão De Probóscideunclassified